Assessment and Educational Quality: Advances, Limitations and Current Challenges - Mejía-Rodríguez, Dania Liz (2021)
This essay discusses current advances, challenges, and limitations about educational assessment and quality. For this purpose, the assessment role in educational processes improvement and their effects on educational quality was identified.  Main findings show that conceptions about assessment and their applications in education have advanced; they have contributed to the continuous progress of education practices. Likewise, educational quality has been related to reflexive changes through contextual practices. However, at present, some limitations on purposes, methods, scopes, and potential uses of assessment for educational quality persist. Hence, challenges relate to the intended, rigorous, and pertinent relationship between assessment and educational improvement.